Sulodexide in the Treatment of Patients with Early Stages of COVID-19: A Randomized Controlled Trial - Gonzalez-Ochoa, Alejandro J.; Raffetto, Joseph D.; Hernández, Ana G.; Zavala, Nestor; Gutiérrez, Obed; Vargas, Arturo; Loustaunau, Jorge (Thrombosis and Haemostasis, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may induce several vascular endothelial-dependent systemic complications, and sulodexide has pleiotropic actions on the vascular endothelium, which may prove beneficial. We aimed to assess the effect of sulodexide when used within 3 days of coronavirus disease 2019 (COVID-19) clinical onset. We conducted a randomized placebo-controlled outpatient trial. To be included, patients must have been at high risk for severe clinical progression. Participants received sulodexide (oral 1,000 LRU/d) or placebo for 21 days. The primary endpoint was the need for hospital care. Also assessed were patients' need for supplemental oxygen as well as D-dimer and C-reactive protein (CRP) levels, thromboembolic events, major bleeding, and mortality. A total of 243 patients were included in the per-protocol analysis from June 5 to August 30, 2020. Of these, 124 received sulodexide and 119 received a placebo. Only 17.7% of the patients in the sulodexide group required hospitalization, compared with 29.4% in the placebo group (p = 0.03). This benefit persisted in the intention-to-treat analysis (15% in sulodexide group vs. 24% with placebo [p = 0.04]). With sulodexide, fewer patients required supplemental oxygen (30 vs. 42% [p = 0.05]). After 2 weeks, fewer patients had D-dimer levels >500 ng/dL (22 vs. 47% [p < 0.01]), and patients also had lower mean CRP levels (12.5 vs. 17.8 mg/dL [p < 0.01]). There were no between-group differences in thromboembolic events, major bleeding, or mortality. Treatment of COVID-19 patients with sulodexide, when provided within 3 days of clinical onset, improved their clinical outcomes. Although the results should be confirmed, sulodexide could be valuable in an outpatient setting.
Keywords: COVID-19; sulodexide; D-dimer; early treatment; SARS-CoV-2; C-reactive protein